Мілітарна ідентичність у контексті соціальної (ре)адаптації ветеранів АТО/ООС - Артеменко, Анна Броніславівна; Artemenko, Anna B. (Харків: Харківський національний університет імені В.Н. Каразіна, 2020)
Artemenko A. B. Military identity in the context of social (re)adaptation of ATO/JFO veterans. – Qualification scholarly paper: a manuscript. Thesis submitted for obtaining the Doctor of Philosophy degree in Social and behavioral sciences, Speciality 054 – Sociology. – Kharkiv University of Humanities “People’s Ukrainian Academy”, Ministry of Education and Science of Ukraine; V. N. Karazin Kharkiv National University, Ministry of Education and Science of Ukraine, Kharkiv, 2020. In the thesis the conceptualization of the social phenomenon of military identity is carried out and its influence on the process of social (re)adaptation of ATO / JFO veterans is studied. From the gnoseological point of view, the relevance of the topic is due to the lack of sociological studies of military identity as a factor of social adaptation of veterans, from the ontological point of view – by public demand for social support of ATO / JFO veterans and study of their postmilitary social positions.
Military identity in the context of social (re)adaptation of ATO/JFO veterans
Робота присвячена концептуалізації соціального феномену мілітарної ідентичності та дослідженню його впливу на процес соціальної (ре)адаптації ветеранів АТО/ООС. Актуальність теми зумовлена браком соціологічних досліджень мілітарної ідентичності як чинника соціальної адаптації ветеранів, а також суспільним запитом на соціальний супровід ветеранів АТО/ООС та оптимізацію їх постмілітарного соціального становища.
Keywords: ветеран АТО/ООС; військовослужбовець; мілітарна ідентичність; соціальна ідентичність; соціальна (ре)адаптація; альтернація; армія; цивільне поле; ATO / JFO veteran; service(wo)man; military identity; social identity; social (re)adaptation; alternation; army; civilian field